A comparative study of HPLC and UV spectrophotometric methods for remdesivir quantification in pharmaceutical formulations. Issue 1 (1st January 2021) - Bulduk, Ibrahim; Akbel, Erten
Abstract : UV spectrophotometric and HPLC methods have been developed and validated for the quantitative determination of remdesivir in pharmaceutical formulations. The HPLC analyzes  have been performed on a C-18 column with a mobile phase consisting of 20 mM KH2 PO4 solution and acetonitrile (50:50, v/v), at a flow rate of 1.2 mL min −1 . UV spectrum has been recorded between 200 and 800 nm using deionized water as solvent and the wavelength of 247 nm has been selected. These  methods have been validated according to the procedures described in ICH guidelines Q2(R1).  Both methods demonstrated good linearity, precision and recovery. No spectral and chromatographic interferences from non-medicinal ingredients were found in both methods. Correlation coefficients were greater than 0.999 within a concentration range of 10–60 mg mL −1 . Therefore both analytical methods gave the most reliable results for the quantification of remdesivir in pharmaceutical formulation.